Versatile gold-silver-PB nanojujubes for multi-modal detection and photo-responsive elimination against bacteria - Zhang, Xining; Xiong, Youlin; Cai, Shuangfei; Wu, Ting; Lian, Zheng; Wang, Chen; Zhang, Wei; Yang, Rong (Frontiers in Chemistry, 2023)
Bacterial infections have become a serious threat to global public health. Nanomaterials have shown promise in the development of bacterial biosensing and antibiotic-free antibacterial modalities, but single-component materials are often less functional and difficult to achieve dual bacterial detection and killing. Herein, we report a novel strategy based on the effective integration of multi-modal bacterial detection and elimination, by constructing the versatile gold-silver-Prussian blue nanojujubes (GSP NJs) via a facile template etching method. Such incorporation of multi-components involves the utilization of cores of gold nanobipyramids with strong surface-enhanced Raman scattering (SERS) activity, the shells of Prussian blue as both an efficient bio-silent SERS label and an active peroxidase-mimic, and functionalization of polyvinyl pyrrolidone and vancomycin, respectively endowing them with good colloidal dispersibility and specificity against S. aureus. The GSP NJs show operational convenience in the SERS detection and excellent peroxidase-like activity for the sensitive colorimetric detection. Meanwhile, they exhibit robust near-infrared photothermal/photodynamic effects, and the photo-promoted Ag+ ions release, ultimately achieving a high antibacterial efficiency over 99.9 % in 5 min. The NJs can also effectively eliminate complex biofilms. The work provides new insights into the design of multifunctional core-shell nanostructures for the integrated bacterial detection and therapy.